Jejak-Jejak Psikologis dalam Tulisan Tangan Bung Karno - Wildan Insan Fauzi; Iing Yulianti (Department of History, Faculty of Humanities, Diponegoro University, 2022)
Reading a person's character through handwriting can be learned through a science called